La peligrosa híper-constitucionalización del Derecho: análisis preliminar del caso peruano - Monge Morales, Gonzalo J. (Pontificia Universidad Católica del Perú, 2025)
This article provides a preliminary analysis, intended to generate academic debate, of the hyper-constitutionalization of Law in Peru, a littlestudied but highly relevant topic of contemporary relevance.If everything is constitutionalized, excesses can be committed. If everything is constitutional, then nothing is. And although contemporary constitutions and the constitutionalism of rights offer merit, the misunderstood constitutionalization of Law can lead to dangers that jeopardize what it was promised to protect: fundamental rights.

Este artículo analiza, de forma preliminar y para generar debate académico, la híper-constitucionalización del Derecho en el Perú, un tema poco estudiado, pero de alta relevancia contemporánea. Si todo se constitucionaliza, se pueden cometer excesos. Si todo es constitucional, entonces nada lo es. Y aunque las Constituciones contemporáneas y el constitucionalismo de los derechos presenten bondades, la constitucionalización del Derecho mal entendida puede llevar a peligros que ponen en riesgo aquello que se prometió proteger: los derechos fundamentales.
The dangerous hyper-constitutionalization of law: a preliminary analysis of the peruvian case
Keywords: Constitutional Law; Constitutionalization; Hyper-constitutionalization; Neoconstitutionalism; Derecho Constitucional; Constitucionalización; Híper-constitucionalización; Neoconstitutionalismo; https://purl.org/pe-repo/ocde/ford#5.05.01